2019
DOI: 10.1016/j.jtumed.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological patterns of primary malignant ovarian neoplasms in different age groups in Almadinah Almunawwarah region, KSA

Abstract: Objectives In the literature, the epidemiological pattern of ovarian neoplasms in different age groups in the Almadinah Almunawwarah region in KSA has not been completely elucidated. Moreover, an unusually frequent diagnosis of adult granulosa cell tumour (AGCT) has been observed in patients in Almadinah Almunawwarah, KSA. This study aimed to describe the pattern of ovarian neoplasms in different age groups in the Almadinah Almunawwarah region with particular emphasis on AGCT. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…6,13,16 However, studies conducted in Nepal, Ghana and Nigeria showed that mature cystic teratoma was the commonest benign ovarian neoplasm. [19][20][21] The most common malignant tumor was serous cystadenocarcinoma and adult granulosa cell tumor, each constituting 3% of the all malignant cases followed by endometrioid adenocarcinoma (2.5%) and mucinous cystadenocarcinoma (2%) which apart from relatively higher incidence of adult granulosa cell tumor in our study, shows a concordance with the literature 20,22 that could be explained related to our study's small sample size, genetic or environmental factors. 3330…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…6,13,16 However, studies conducted in Nepal, Ghana and Nigeria showed that mature cystic teratoma was the commonest benign ovarian neoplasm. [19][20][21] The most common malignant tumor was serous cystadenocarcinoma and adult granulosa cell tumor, each constituting 3% of the all malignant cases followed by endometrioid adenocarcinoma (2.5%) and mucinous cystadenocarcinoma (2%) which apart from relatively higher incidence of adult granulosa cell tumor in our study, shows a concordance with the literature 20,22 that could be explained related to our study's small sample size, genetic or environmental factors. 3330…”
Section: Discussionsupporting
confidence: 89%
“…One-sided (75.7%) tumors were more common than bilateral (7.3%) and right ovarian involvement (42.4%) was more common than the left (33.3%), which was in concordance with findings of studies conducted in India, Iraq, and Bangladesh. 10,17,22,23 In terms of tumor consistency, 72.7% were cystic, 11.1% solid and 15.7% complex and only one case (0.5%) was not assessable due to diffuse pattern of the tumor. Tumors with cystic consistency were mostly benign constituting 88.3%, while malignant tumors were either solid or complex, each being 42.4% and 51.5%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Out of all neoplastic lesions, our results show that benign ovarian neoplasms were 64.4%, while the percentages of borderline and malignant neoplasms were 6.2% and 29.4%, respectively. Yousif et al had approximately similar findings in their patient population, which were 63% for benign, 7% for borderline, and 30% for malignant [ 19 ]. Abdullah and Bondagji found that the percentages of benign, borderline, and malignant neoplasms were 72.8%, 5.2%, 22%, respectively [ 13 ].…”
Section: Discussionmentioning
confidence: 77%
“…Serous cystadenoma and serous cystadenocarcinoma are the most prevalent benign and malignant ovarian neoplasms, respectively. Malignant ovarian neoplasms are more common as people get older [1]. Another study in Riyadh indicated that most neoplastic ovarian tumors in children and adolescents are benign [2].…”
Section: Resultsmentioning
confidence: 99%
“…Ovarian carcinoma is the second most prevalent cancer of the female reproductive system and the fifth leading cause of cancer-related death in women. Ovarian cancer is the sixth most frequent cancer in Saudi women, with a mean age at diagnosis of 54 years and a wide age range of 5 to 97 years [1]. Globally, the prevalence varies.…”
Section: Introductionmentioning
confidence: 99%